2016
DOI: 10.5604/12303666.1215541
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Functionalization of Textile Materials with Copper Silicate

Abstract: A biofunctionalization of nonwoven fabrics was carried out with 0.1-4 wt.% of copper silicate. Polypropylene (PP), polyethylene (PE) and biodegradable polymers [poly(lactic acid) (PLA), polyhydroxyalkanoates (PHA)] or their mixtures were used as polymer components. Mostly liquid oligomers of ethylene glycol (PEG) or copolymers of ethylene oxide and propylene oxide (2.5-5 wt.%) were applied as plasticizers. New composite nonwovens containing CuSiO 3 were prepared by the melt-blown technique [1]. They showed ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…Substantial importance in this field is played by PLA composites equipped with antibacterial additivities, in the majority organic bactericides (e.g., ampicillin [ 9 ] chlorhexidine [ 10 , 11 ], ciprofloxacin [ 12 , 13 ], doxycyclin [ 14 ], gentamycin [ 15 ], oflaxin and vancomycin [ 16 ], triclosan [ 17 , 18 , 19 ], and/or curcumin [ 20 ], etc.). Due to an established role of metal nanoparticles in medicine [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ], the group of increasing importance is PLA-inorganic hybrids [ 34 ], due to their high antibacterial efficiency, simplicity and also low cost of technological preparation.…”
Section: Introductionmentioning
confidence: 99%
“…Substantial importance in this field is played by PLA composites equipped with antibacterial additivities, in the majority organic bactericides (e.g., ampicillin [ 9 ] chlorhexidine [ 10 , 11 ], ciprofloxacin [ 12 , 13 ], doxycyclin [ 14 ], gentamycin [ 15 ], oflaxin and vancomycin [ 16 ], triclosan [ 17 , 18 , 19 ], and/or curcumin [ 20 ], etc.). Due to an established role of metal nanoparticles in medicine [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ], the group of increasing importance is PLA-inorganic hybrids [ 34 ], due to their high antibacterial efficiency, simplicity and also low cost of technological preparation.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research works with pure PP and pure PLA nonwovens functionalized with CuO⋅SiO 2 revealed that 0.1% and 0.25% CuO⋅SiO 2 content did not provide sufficient antimicrobial activity, especially towards Candida albicans [17]. In that case the use of at least 0.5% of this additive was needed.…”
Section: Nonwovens Compositionmentioning
confidence: 97%
“…As part of our research program directed on biologically active functionalized phosphonates [59][60][61][62][63], and their grafting on polymer matrix [64,65], we present the preparation, and physico-chemical and biological properties of PLA-FOS polymer hybrid.…”
Section: Artificialmentioning
confidence: 99%